PENGARUH LIKUIDITAS, RISIKO KREDIT, DAN PERMODALAN TERHADAP PROFITABILITAS PADA SEKTOR PERBANKAN DI BURSA EFEK INDONESIA - Krisna, Kadek Nova Priana; Candradewi, Made Reina (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.11.TAHUN.2024, 2024)
Profitability is one of the financial ratios that can be used as the main indicator to assess the financial performance of a company. The level of profitability of a banking company can provide an in-depth picture of its financial health and operational sustainability in the long term. This study aims to examine the effect of liquidity, credit risk, and capital on profitability. This research was conducted at banking sector companies listed on the Indonesia Stock Exchange for the period 2019-2022, with a total sample of 38 companies obtained using purposive sampling method. The data analysis technique used is multiple linear regression analysis with the IBM SPSS version 26 program tool. The results of the analysis show that 1) liquidity has a positive and significant effect on profitability, 2) credit risk has a negative and significant effect on profitability, 3) capital has a positive and significant effect on profitability. The implication of this research is that company management in the banking sector should pay attention to factors such as liquidity, credit risk, and capital in an effort to increase company profitability. This is due to the results of research showing that these three factors have a significant influence on the profitability of banking sector companies.